2011
DOI: 10.1080/07347332.2011.615382
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness: Existential, Loss, and Grief Factors in Women with Breast Cancer

Abstract: Although a plethora of studies exist as to the efficacy of mindfulness-based interventions with cancer patients, existential, loss, and grief factors are absent. The primary purpose of this exploratory study was to add to the literature by exploring the pre-post effects of an 8-week mindfulness-based intervention on existential well-being, summed self-identified losses, and grief scores as well as assess mental adjustment to cancer; also, 6-month follow-up data as to intervention maintenance were obtained. Six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 35 publications
0
36
0
3
Order By: Relevance
“…Those individual living with distress may demonstrate varying degree of social isolation, detaching themselves from their social circle, resulting in declining mental wellness. 19,20 With the growing population of women surviving many years after breast cancer treatments, there is a need to assess not only clinical outcomes or screening for cancer antigens but also the physical and psychological aspects of quality of life in women breast cancer survivors after losing their breast. 21 Therefore, health care professionals should understand the possible impact of altered body image so as to play an important supportive role in the women's transition from cancer treatment into survivorship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those individual living with distress may demonstrate varying degree of social isolation, detaching themselves from their social circle, resulting in declining mental wellness. 19,20 With the growing population of women surviving many years after breast cancer treatments, there is a need to assess not only clinical outcomes or screening for cancer antigens but also the physical and psychological aspects of quality of life in women breast cancer survivors after losing their breast. 21 Therefore, health care professionals should understand the possible impact of altered body image so as to play an important supportive role in the women's transition from cancer treatment into survivorship.…”
Section: Discussionmentioning
confidence: 99%
“…Women breast cancer survivors may be medically well but living with a negative perception of their post‐cancer body image leading to psychosocial distress. Those individual living with distress may demonstrate varying degree of social isolation, detaching themselves from their social circle, resulting in declining mental wellness . With the growing population of women surviving many years after breast cancer treatments, there is a need to assess not only clinical outcomes or screening for cancer antigens but also the physical and psychological aspects of quality of life in women breast cancer survivors after losing their breast .…”
Section: Introductionmentioning
confidence: 99%
“…Other outcomes assessed include cancer-related symptoms such as fatigue, pain, and sleep [17, 18], and existential outcomes including spirituality, posttraumatic growth, loss, and grief [19, 132], as well as various measures of mindfulness [12, 2022]. …”
Section: Clinical Populationsmentioning
confidence: 99%
“…These wide ranging appearance changes can be a significant source of distress and body dissatisfaction for women (Falk Dahl et al, 2010;Helms et al, 2008), particularly because they are out of the individual's control (Tacon, 2011). Indeed, one study reported appearance concerns among 17% to 33% of women within 7 months of their diagnosis (Fobair et al, 2006).…”
Section: What Is the Impact Of An Altered Appearance For Women With Bmentioning
confidence: 99%